Penyusunan Laporan Pertanggung Jawaban (LPJ) Bendahara Pengeluaran pada Kantor Pelayanan Perbendaharaan Negara Curup - Berlian Afriansyah (Jurnal Ilmiah Raflesia Akuntansi, 2019)
This research is to know the compilation of Expenditure Accountant Account Statement at KPPN Curup in order to be accountable to the use of fund in accordance with established theory. The analysis used in this research is descriptive analysis method. The result of the research can be concluded that KPPN Curup in the bookkeeping of Spending Treasurer has used the application issued by the Minister of Finance that is SILABI. At the time of internal reconciliation, there was a difference in cash in the Spending Treasurer. The UAKPA report is limited to UP balances, while the Treasurer's report covers all cash balances available to the treasurer. Submission of Liabilities of Spending Treasurer Account shall be executed no later than the tenth of the following month. In the event that the submission of the Spending Treasurer's Account Statement exceeds the stipulated time limit, KPPN shall impose sanctions in the form of postponement of SP2D issuance of SPM- UP / SPM- TUP / SPM- GUP or SPM- LS filed by the Spending Treasurer.